A influência dos valores humanos na determinação das âncoras de carreira - Abrahim, Gisele Seabra (2008)
The general objective of this work is to analyze the influence of the human values in the determination of the career anchors based on the idea that the professional predisposition receives influence from the cognitive central system; in other words, the values, which are conceived as a form of criteria capable of influencing actions, choices and the human behavior, interfering in the way each individual judges himself and others. In this sense, the human values affect the actions of the individuals on their work; and allied to the motivations and to the talent they stimulate the decisions over the career (SCHEIN, 1993). The studies of the Massachusetts Institute of Technology (MIT) identified eight categories of professional inclinations, also called career anchors, which are stimulated by appetites, feelings and necessities and are established from the construction of the auto-concept (SCHEIN, 1993). From this perspective, it s possible to infer the existence of a narrow relationship between the human values and the career anchors. Facing this idea, do individuals with the same career anchors tend to prioritize the same human values? As the driver line of this investigation, the hypothesis that individuals with the same career anchors prioritize, in a similar way, the human values that guide their behavior, was launched. In this sense, the theoretical referential background of this research presents a system of definitions based on the studies of Schein (1993; 1996; 2006th; 2006b; 2006c) and Rokeach (1979; 1981) on careers and values because of the importance of their studies for each area of knowledge and for the international repercussion of their work, which favored the validation of the instruments of inquiry hereby used: the questionnaire of career anchors and the Rokeach Value Survey. The methodology is based on the type of correlation analysis between two variables: values and career anchors. The inquiry in locus was divided into two parts. In the first one, took place the simultaneous application of the two mentioned instruments in a sample of 100 university students of the courses of business administration and accountancy, of the Centro Universitário do Pará (CESUPA) and of the Pontifícia Universidade Católica de São Paulo (PUC-SP). In the second part, interviews were carried out with a person of each career anchor, with the exception of the general management competence since the results reached in the first stage were sufficient to attend the objective here drawn. The proceedings of analysis of these data include, besides the analysis of the content of the interviews and of the descriptions of the professional inclinations, some statistical tests such as Pearson's correlation coefficient and chi-square distribution, both applied to check the association between the variables of this inquiry. The correlation of the data obtained through the use of the above-mentioned instruments of inquiry demonstrates coherence with the formulated hypothesis, since the individuals with the same professional inclinations attributed similar grades to their respective hierarchies of values, above all when the values that can be tied to the characteristics inherent in each anchor are isolated, which are present in the theoretical content of Schein and in the testimonies of the interviewed ones. Though the results of the correlation tests presented moderate signification, they made possible the identification of the most and the least inclined human values of receiving bigger importance by the individuals inside the different categories of career anchors. In this sense, the conclusion of this investigation reinforces the influence of the human values in the decisions of career